Evaluation of right ventricular function in patients with propionic acidemia: a cross-sectional study - Kovacevic, Alexander; Garbade, Sven; Hörster, Friederike; Hoffmann, Georg F.; Gorenflo, Matthias; Mereles, Derliz; Kölker, Stefan; Staufner, Christian (Children, 2023)
In propionic acidemia (PA), myocardial involvement often leads to progressive cardiac dysfunction of the left ventricle (LV). Cardiomyopathy (CM) is an important contributor to mortality. Although known to be of prognostic value in CM, there are no published data on right ventricular (RV) function in PA patients.
Gesehen am 14.11.2023